A Biomarker for Concussion: The Good, the Bad, and the Unknown. (30th December 2019) - Reece, Jenna T; Milone, Michael; Wang, Ping; Herman, Daniel; Petrov, Dmitriy; Shaw, Leslie M
Abstract: Background: Traumatic brain injury (TBI) is a significant cause of morbidity, mortality, and disability in the US, with >2.8 million patients presenting to the emergency department (ED) annually. However, the diagnosis of TBI is challenging and presents a number of difficulties, particularly at the mildest end of the spectrum: concussion. A number of groups have researched biomarkers to aid in the evaluation of TBI, and most recently in 2018 the Food and Drug Administration approved a new blood-based immunoassay biomarker using ubiquitin carboxyl hydrolase L1 and glial fibrillary acidic protein to aid in head computed tomography (CT) triage. Content: This review clarifies the practical challenges in assessing and implementing a new blood biomarker. It then examines the clinical context and need, as well as the evidence used to validate this new immunoassay. Summary: Concussion is a multifaceted diagnosis with a need for biomarkers to assist in diagnostic and prognostic assessment. Recent articles in the lay press have revealed misunderstanding about the function of this new test, expressing hopes that this biomarker serves patients at the mildest end of the spectrum and is useful for athletes and children. None of these assumptions are correct, as this biomarker has been evaluated in patients only at the moderate end of the spectrum and has been validated only in adults presenting to the ED who have already been triaged to receive head CT, not in athletes or children. The next steps for this assay should consider clinical work flow and clarifying its intended use, including integration with existing triage methods, and validating the assay for a broader population.